Konsep Proses Pemesinan Berkelanjutan - Gusri Akhyar Ibrahim (JURNAL MECHANICAL, 2013)
Metal industrial machining usually strongth pressure from all sectors, ether raw material industries or user metal industries. Manufacturint process which offered to all sectors industries  or companies that sustainable manufakturing consist of three main factor are efective cost, enviroment and social performance. Keywords: Sustainable, machining, social, enviroment, cost.